In-vitro analysis of the expression of TGFbeta -superfamily-members during chondrogenic differentiation of mesenchymal stem cells and chondrocytes during dedifferentiation in cell culture - Gößler, Ulrich; Bugert, Peter; Bieback, Karen; Deml, Moritz Caspar; Sadick, Haneen; Hörmann, Karl; Riedel, Frank (Cellular & molecular biology letters, 2005)
Traditional surgical methods for the reconstruction of cartilage defects rely on the transplantation of autologous and allogenous tissues. The disadvantages of these techniques are the limited availability of suitable tissues and the donor site morbidity of transplants. In addition, in cultured chondrocytes, the dedifferentiation of cells seems unavoidable during multiplication. In this study, we investigated the expression of distinct markers during the dedifferentiation of human chondrocytes (HC) and human mesenchymal stem cells (MSC) in cell culture using microarray technique, immunohistochemistry and RT-PCR. Transforming growth factor beta (TGFbeta) is a multifunctional peptide that plays play a crucial role in inducing and maintaining chondrogenic differentiation. In dedifferentiating chondrocytes, the gene for TGFbeta1 was constantly expressed, while the gene for TGFbeta2 was never expressed. The genes for TGFalpha, TGFbeta4 and TGFbetai were activated with ongoing dedifferentiation. TGFbeta-receptor 3 was constantly expressed, while the genes for the TGFbeta-receptors 1 and 2 were never expressed. Immunohistochemical staining for TGFbeta beta 3 revealed upregulation in the course of dedifferentiation. The genes for LTBP1 and LTBP2 were activated with ongoing dedifferentiation, whereas the gene for LTBP3 was constantly expressed, and negative results were obtained for the gene for LTBP4. The genes for LTBP1 and LTBP2 were activated with ongoing dedifferentiation. During chondrogenic differentiation, the MSCs constantly expressed TGFbeta1, beta2, beta3 and beta4. LTBP1, LTBP2 and TGFbeta-R3 were downregulated. In conclusion, TGFbeta3, TGFbeta4, TGFbetai, LTBP1 and LTBP2 may assist the process of dedifferentiation, while TGFbeta1 and beta2 might not be involved in this process. Of the TGFbeta-receptors, only type 3 might be involved in dedifferentiation.
Gesehen am 01.04.2022